PSYCHOLOGICAL MANIFESTATIONS IN CHILDREN WITH NEPHROGENIC DIABETES INSIPIDUS AND SEVERE MALNUTRITION: BORDERLINE INTELLECTUAL FUNCTIONING, BULLYING, LOW SELF-ESTEEM, AND DEPRESSIVE SYMPTOMS - Ni Nyoman Tri Pramayanti; I Gusti Ayu Indah Ardani (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT Nephrogenic Diabetes Insipidus (NDI) is a rare metabolic disorder caused by the kidneys’ inability to respond to antidiuretic hormone, resulting in polyuria, polydipsia, and recurrent dehydration, which affect nutritional status and child growth. This condition becomes more complex when accompanied by severe protein energy malnutrition (PEM) of the marasmus type and stunting, which may lead to cognitive and psychosocial impairments. This study aims to examine the relationship between chronic medical conditions, malnutrition, and psychological disorders in adolescents with NDI. The method used is a case report through anamnesis, physical examination, nutritional status evaluation, and psychometric assessments. The subject is a 15-year-old male adolescent with a history of NDI and severe malnutrition. The results show an IQ score of 83, indicating Borderline Intellectual Functioning (BIF), a high score on the Olweus Bullying Questionnaire (≥3) indicating victimization, a Rosenberg Self-Esteem Scale score of 24 indicating low self-esteem, and a Child Depression Inventory score of 26 indicating depressive symptoms. The patient also experienced emotional symptoms such as irritability, anxiety, and social withdrawal. These findings indicate that the combination of chronic illness and malnutrition increases the risk of psychosocial disorders through internal factors (cognitive dysfunction) and external factors (bullying and stigma). It is concluded that a multidisciplinary approach including medical management, nutritional rehabilitation, psychological support, and family and school education is essential to improve quality of life and prevent long-term consequences. ABSTRAK Nephrogenic Diabetes Insipidus (NDI) merupakan gangguan metabolisme langka akibat ketidakmampuan ginjal merespons hormon antidiuretik yang menyebabkan poliuria, polidipsia, dan dehidrasi berulang, serta berdampak pada status gizi dan pertumbuhan anak. Kondisi ini menjadi lebih kompleks karena disertai Protein Energy Malnutrition (PEM) tipe marasmus dan stunting yang berpotensi menimbulkan gangguan kognitif dan psikososial. Penelitian ini bertujuan mengkaji keterkaitan antara kondisi medis kronis, malnutrisi, dan gangguan psikologis pada remaja dengan NDI. Metode yang digunakan adalah studi kasus melalui anamnesis, pemeriksaan fisik, evaluasi status gizi, dan asesmen psikometrik. Subjek adalah remaja laki-laki usia 15 tahun dengan riwayat NDI dan malnutrisi berat. Hasil menunjukkan skor IQ 83 yang mengindikasikan Borderline Intellectual Functioning (BIF), skor Olweus Bullying Questionnaire (OBQ) (≥3) sebagai korban perundungan, skor Rosenberg Self-Esteem Scale 24 (harga diri rendah), serta skor Child Depression Inventory 26 yang menunjukkan gejala depresi. Pasien juga mengalami gejala emosional seperti mudah marah, cemas, dan menarik diri dari lingkungan sosial. Temuan ini menunjukkan bahwa kombinasi penyakit kronis dan malnutrisi meningkatkan risiko gangguan psikososial melalui faktor internal (disfungsi kognitif) dan eksternal (perundungan dan stigma). Disimpulkan bahwa pendekatan multidisiplin yang meliputi penanganan medis, rehabilitasi nutrisi, dukungan psikologis, serta edukasi keluarga dan sekolah sangat diperlukan untuk meningkatkan kualitas hidup dan mencegah dampak jangka panjang.